Making sense of environmental sequencing data: Ecologically important functional traits of the protistan groups Cercozoa and Endomyxa (Rhizaria). (25th November 2019) - Dumack, Kenneth; Fiore‐Donno, Anna Maria; Bass, David; Bonkowski, Michael
Abstract: We have compiled a database of functional traits for two widespread and ecologically important groups of protists, Cercozoa and Endomyxa (Rhizaria). The functional traits of microorganisms are crucially important for interpreting results from environmental sequencing surveys. Linking morphological and ecological traits to environmental factors is common practice in studies involving micro‐ and macroorganisms, but is rarely applied to protists. Our database provides functional and ecologically significant traits linked to morphology, nutrition, locomotion and habitats. We discuss how the use of functional traits may help to unveil underlying ecosystem processes. This database is intended as a common reference for the molecular ecology community and will boost the understanding of ecosystem functions, especially those driven by biological interactions.